Long Non-coding RNA LincRNA-EPS Inhibits Host Defense Against Listeria monocytogenes Infection - Agliano, Federica; Fitzgerald, Katherine A.; Vella, Anthony T.; Rathinam, Vijay A.; Medvedev, Andrei E. (Frontiers in Cellular and Infection Microbiology, 2020)
Long noncoding RNAs (lncRNAs) have emerged as key regulators of gene expression in several biological systems. The long intergenic RNA-erythroid pro-survival (lincRNA-EPS) has been shown to play a critical role in restraining inflammatory gene expression. However, the function of lincRNA-EPS during bacterial infections remains unknown. Here, we demonstrate that following infection with the intracellular bacterium Listeria monocytogenes, both mouse macrophages and dendritic cells lacking lincRNA-EPS exhibit an enhanced expression of proinflammatory cytokine genes, as well as an increased expression of the inducible nitric oxide synthase (iNos) and nitric oxide (NO) production. Importantly, we found that lincRNA-EPS-/- mice intraperitoneally infected with L. monocytogenes exhibit lower bacterial burdens in spleen and liver and produce more NO than control mice. Furthermore, lincRNA-EPS-/- mice are less susceptible to a lethal dose of L. monocytogenes than wild type (WT) mice. Collectively these findings show that lincRNA-EPS suppresses host protective NO expression and impairs the host defense against L. monocytogenes infection.